Long‐Term Study of Hepatitis Delta Virus Infection at Secondary Care Centers: The Impact of Viremia on Liver‐Related Outcomes - Kamal, Habiba; Westman, Gabriel; Falconer, Karolin; Duberg, Ann‐Sofi; Weiland, Ola; Haverinen, Susanna; Wejstål, Rune; Carlsson, Tony; Kampmann, Christian; Larsson, Simon B.; Björkman, Per; Nystedt, Anders; et al. (Hepatology (Baltimore, Md.), 2020)
Background and Aims Hepatitis delta virus (HDV) infection is associated with fast progression to liver cirrhosis and liver complications. Previous studies have, however, been mainly from tertiary care centers, with risk for referral bias toward patients with worse outcomes. Furthermore, the impact of HDV viremia per se on liver‐related outcomes is not really known outside the human immunodeficiency virus co‐infection setting. We have therefore evaluated the long‐term impact of HDV viremia on liver‐related outcomes in a nationwide cohort of patients with hepatitis B and D co‐infection, cared for at secondary care centers in Sweden. Approach and Results In total, 337 patients with anti‐HDV positivity, including 233 patients with HDV RNA viremia and 91 without HDV viremia at baseline, were retrospectively studied, with a mean follow‐up of 6.5 years (range, 0.5‐33.1). The long‐term risks for liver‐related events (i.e., hepatocellular carcinoma [HCC], hepatic decompensation, or liver‐related death/transplantation) were assessed, using Cox regression analysis. The risk for liver‐related events and HCC was 3.8‐fold and 2.6‐fold higher, respectively, in patients with HDV viremia compared with those without viremia, although the latter was not statistically significant. Among patients with HDV viremia with no baseline cirrhosis, the cumulative risk of being free of liver cirrhosis or liver‐related events was 81.9% and 64.0% after 5 and 10 years of follow‐up, respectively. This corresponds to an incidence rate of 0.04 cases per person‐year. Conclusions HDV RNA viremia is associated with a 3.8‐fold higher risk for liver‐related outcomes. The prognosis was rather poor for patients with HDV viremia without cirrhosis at baseline, but it was nevertheless more benign than previous estimates from tertiary centers. Our findings may be of importance when making decisions about treatment and evaluating potential outcomes of upcoming antivirals against HDV.